KEMAMPUAN PEMERINTAH DESA DALAM MENGELOLA DANA DESA - Mulyono Mulyono; Abd Rahman; Ulfah Attamimi (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2021)
The implementation of Law Number 6 of 2014 has provided opportunities for village governments to realize independence in the field of development. This policy demands readiness by the village government to be able to manage village finances so that it can be realized according to the mandate of the regulation. This study describes the ability of the village government in managing village funds in Mendikonu Village, Amonggedo District, Konawe Regency. The research approach is qualitative, where data is collected through observation and interviews. Furthermore, the data were analyzed qualitatively with a descriptive description to answer the research problem. The findings in the study show that the ability of the apparatus in the process of managing village funds starting from financial planning, financial implementation, financial administration, and financial accountability has been running, although not yet optimally. This is due to the limited ability of village government officials and fund managers, especially in terms of knowledge, skills and attitudes.